Applying CAD/CAE/CAM Techniques for Optimizing the Design and Reducing the Cost of a Pediatric Stander - Arenas Calvo, Carlos Ernesto (2023)
A pediatric stander is an adapted piece of equipment whose function is to achieve the vertical position of the child when motor control is inadequate, in other words, when the child cannot stand and control his weight against gravity, having the age to do it. This technical equipment is necessary for patients diagnosed with cerebral palsy who have already acquired head control and initiated trunk control. This product has a high value in Peru. For the generation of this equipment, we will apply a computer editing and design process, we will follow a 5-step process in addition to applying CAD, CAE, and CAM techniques, emphasizing the design optimization method. Finally, we will verify how the application of this methodology, together with computer simulation, allows us to generate a functional, resistant prototype and, in the main point, with optimization in design and acquisition costs.